Ensaio psicanalítico da experiência psíquica em festas raves - Mendes, Cristianne Macedo (2010)
This study examines the rave phenomenon, as an organization of contemporary youth culture. Became interesting to study the phenomenon in question and know more about the cultural moment in which we live, as it is specific to modernity, despite having features of the youth of yesteryear. The work also addresses the peculiarities of electronic music, the concepts of sacrifice and feasts, presents a comparison of raves with rituals of Indian tribe and an analysis of the discursive production of some ravers from psicanlíticos concepts. This study might reveal in an interesting speech production cycle is the presentation of the idealized pursuit of pleasure and freedom in the rave experience disappointment, finishing with a more realistic understanding of the same experience as subjetiva.Utilizaram is, as the main reference in this analysis, Freud's texts